Calvyn, Servet en ons ... teologie, geskiedenis en die negende gebod - V. E. d'Assonville (Acta Theologica)
The case of Servet has not only been the subject of extensive investigation in church history often, but is also a case about which there has always been much speculation. However, even in works of a scientific nature, the religious, cultural, historical and juridical gap between the 16th and the 20th/21st centuries is not being reflected on sufficiently. Aspects that should be taken into consideration are inter alia of a political, juridical, moral, theological and ecumenical nature. By way of taking at least these aspects into regard and by pursuing the principle of ad fontes consequently, one can prevent neglecting the 9th Commandment in theological and historical studies.